2010
DOI: 10.1097/mco.0b013e328337d925
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support for extremely low-birth weight infants: abandoning catabolism in the neonatal intensive care unit

Abstract: Despite the fact that substantially improved nutritional therapies for preterm neonates have been implemented, still, some reluctance exists when it comes to providing high amounts of nutrition to the most immature infants. Pros and cons are outlined, as well as deficits in knowledge, when it comes to providing the optimal nutrient strategy in the first postnatal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 104 publications
(92 reference statements)
0
19
0
1
Order By: Relevance
“…A stepwise increase and/or a delayed [13] commencement of nutrient administration inevitably result in the occurrence of considerable deficits during the first few days of life [4]. These deficits have proven to be very hard to recoup and every effort should be made to prevent their occurrence [29]. …”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…A stepwise increase and/or a delayed [13] commencement of nutrient administration inevitably result in the occurrence of considerable deficits during the first few days of life [4]. These deficits have proven to be very hard to recoup and every effort should be made to prevent their occurrence [29]. …”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%
“…For example, reference urea concentrations in the fetus range from 7.5 to 14.3 mmol/l [34]. Effects of higher urea concentrations are unclear [29], although urea concentrations >30 mmol/l were accompanied with slightly elevated ammonia concentrations of around 100 µmol/l in premature infants below 24 weeks of gestation receiving up to 4 g amino acids/kg per day during the first few days of life [35]. However, in most NICUs, urea cutoff values for discontinuing or decreasing parenteral amino acids are much lower.…”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%
“…Ehrenkranz et al showed that the severity of illness as well as the early nutrition practices are both, independently, associated with both survival and neurodevelopmental outcome at discharge and two years of age [10]. Another study showed that not only psychomotor development improved by giving more protein to preterm infants, also was the incidence of infections lower [24]. At the same time however, there might also be an upper limit to the intake of protein and calories in the neonatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these approaches still leave infants with resultant postnatal growth restriction as reviewed by Ziegler [9]. Postnatal growth restriction has been associated with adverse long-term neurocognitive outcomes [10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%